Proceedings of Eurosensors 2017, Paris, France, 3–6 September 2017 2017
DOI: 10.3390/proceedings1040398
|View full text |Cite
|
Sign up to set email alerts
|

Use of Gas Sensors and FOBT for the Early Detection of Colorectal Cancer

Abstract: Among the major challenges of medicine today there are screening and early detection of tumors (since the adenoma stage) in order to prevent their degeneration into malignant cancer and/or metastases. In particular, the colorectal cancer shows a high curability rate, up to 90%, if identified when in its benign stage. The Protocol discussed here is proposed to implement the clinical validation of a device consisting of an array of chemoresistive gas sensors made of semiconductor materials, able of identifying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Comparable results were reported using SIFT-MS, which differentiated patients affected by CRC and advanced adenoma from healthy controls with an accuracy of 75% (72% sensitivity and 78% specificity) [47]. More recently, the eNose Scent A1 performed even better in a relatively large cohort of patients (86 CRC and 71 controls) (Table 3) [48].…”
Section: Fecal Vocsmentioning
confidence: 73%
“…Comparable results were reported using SIFT-MS, which differentiated patients affected by CRC and advanced adenoma from healthy controls with an accuracy of 75% (72% sensitivity and 78% specificity) [47]. More recently, the eNose Scent A1 performed even better in a relatively large cohort of patients (86 CRC and 71 controls) (Table 3) [48].…”
Section: Fecal Vocsmentioning
confidence: 73%
“…For this reason, a screening method based on the detection of tumor biomarkers, not directly related to occult blood (e.g., VOCs), can be useful to discriminate between CRC false and true positives resulting from FIT. A preliminary study, used to finalize the device, the best sensor array (shown in Table 2), and the analysis protocol, has been performed (in collaboration with the Department of Radiology and Section of General and Thoracic Surgery of the S. Anna Hospital of Ferrara) on fecal samples from CRC-affected patients (extracted during surgery) and from healthy volunteers [134]. As an example, the chosen sensors were successfully able to discriminate the health status of the subjects according to the Principal Component Analysis (PCA; Figure 19).…”
Section: Tumor Screeningmentioning
confidence: 99%
“…On one hand, Gas chromatography-mass spectrometry (GC-MS), which is a chemical analytical technique, is considered the ongoing gold standard in VOC detection [52], but on the other hand, VOC sensors are getting more and more relevance because they are inexpensive, often portable, and easy to use [109]. This is why findings such as the ones listed in Table S7 (Supplementary material) could represent the next frontier for large population-based screening programs [50][51][52][53][54][55][56][57][58].…”
Section: Volatile Organic Compounds (Vocs) 271 Stool Vocsmentioning
confidence: 99%
“…Among them, SCENTA1 ® [58], that works using a pattern-recognition technology and was recently patented by Zonta et al [57], showed remarkable sensitivity and specificity (95%). The authors suggest that the addition of a technology that relies on a gaseous marker, totally different from occult blood, as a complementary test could drastically reduce false positive rates.…”
Section: Volatile Organic Compounds (Vocs) 271 Stool Vocsmentioning
confidence: 99%
See 1 more Smart Citation